Konflik Masyarakat Di Kelurahan Mancani Kota Palopo - Nurlindah Nurlindah; Andi Agustang; Najamuddin Najamuddin (Universitas Negeri Makassar, 2022)
This study aims to determine how the dynamics of conflict in the community in the Mancani Village, Palopo City. The type of research used is qualitative research with a case study method or approach. The technique of determining informants was done by purposive sampling with the criteria of informants, namely the population involved in the conflict, the local government and the security forces, totaling 8 people. Data collection techniques were carried out by means of observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validation technique used is source triangulation. The results of the study reveal that the dynamics of community conflict in Mancani Village, Palopo City, namely conflict begins with personal conflict and then spreads to group conflict, the main factor being triggered by the influence of alcohol, lack of parental guidance, juvenile delinquency, and ineffective efforts made by the government. Various efforts have been made by the government in resolving the conflict, such as structural handling and customary handling. However, these efforts have not been able to overcome the conflicts in the Mancani Village.